PLATO: a practice development approach to reconsidering student learning partnerships - Claire Hamshire (Foundation of Nursing Studies, 2021)
Background: This article explores the use of a practice development approach to support nursing students’ engagement in learning partnerships in clinical practice settings. Aim: To reflect, using the model proposed by Rolfe and colleagues (2001), on the development of ‘PLATO’ – an educational tool to help nursing students explore their role in building learning partnerships in clinical settings. Conclusion: A practice development approach to clinical learning partnerships can support an effective learning culture. As a result, nursing students can gain greater empowerment and take increased responsibility for their learning. Implications for practice: • Facilitating learning partnerships with students is important for achieving person-centred care • Partnership working provides opportunities for true collaboration and for learning with and from our students • Developing collaborative spaces can facilitate nursing students to reflect in and on their practice